Length-weight relationship of Sphyraena obtusata cuvier, 1829 (Pisces: Perciformes) from the Jaffna Lagoon, Sri Lanka - Sivashanthini, K.; Gayathri, G.; Gajapathy, K. (Academic Journals Inc, 2009)
The present study was carried out to gain some knowledge on length-weight relationship parameters, growth pattern and difference between the growth parameters of male and female Spltyraena obtusata. The knowledge of length-weight relationship has numerous practical applications in fishery biology. Such a mathematical equation enables conversion of one parameter in to another as is often required during monitoring field measurements. Length weight regression equations were derived for make and female estimated by using the logarithms of the total lengths and the corresponding weights. The curvilinear relationships of length-weight relationships for male and female were W=0.0117*L2.896 and W=0.0138*L2.843, respectively. Covariance analysis for length-weight relationships of males and females revealed that there is no significant difference (p>0.05) between male and female and hence a common formulae of W=0.0133*TL2.857 was derived for S. obtusata, The 'b' values 2.898 and 2.843 obtained for male and female respectively indicate that the fish follows the cube law and its growth is negative allometry.
Keywords: Cube law; Growth; Jaffna lagoon; Obtuse barracuda; Regression coefficients